A guide to the African human rights system: Celebrating 30 years since the entry into force of the African Charter on Human and Peoples' Rights 1986 - 2016 Edited by Centre for Human Rights, Faculty of Law, University of Pretoria - Edited by Centre for Human Rights, Faculty of Law, University of Pretoria (Pretoria University Law Press (PULP), 2016)
A guide to the African human rights system: Celebrating 30 years since the entry into force of the African Charter on Human and Peoples' Rights 1986 - 2016 Edited by Centre for Human Rights, Faculty of Law, University of Pretoria 2016 ISBN: 978-1-92053-56-9 Pages: 80 Print version: Available Electronic version: Free PDF available